RESPON PEMBERIAN KOMPOS DENGAN BIODEKOMPOSER TERHADAP PERTUMBUHAN VEGETATIF CABAI RAWIT HIYUNG (Capsicum spp.) - Eva Ristawati; Antar Sofyan; Akhmad Gazali (Agroekotek View, 2019)
Compost is a term for human processed organic fertilizers made from a process of decaying remains of living things (plants and animals). The process of making composter is divided into aerobes and anaerobes which support each other in certain environmental conditions, which as a whole is called decomposition (Yuwono, 2006). Hiyung cayenne (Capsicum spp) is a local cayenne pepper from Hiyung village, Tapini Tengah i sub-district, Tapin Regency, South Kalimantan. This study aims to determine growth response and i determine i the i most appropriate dose i for i growth i of i the i vegetative phase of Hiyung cayenne (Capsicum spp.). This research was conducted in experimental park of Wahana Kalimantan Institute, Loktabat Utara, Banjarbaru, South Kalimantan, from June until October 2018. This i study i used i was Randomized i Complete i Block i Design i (RCBD) of one i factor i consisting i of i 5 (five) treatments and 5 (five) repetitions to obtain 25 experimental units. The treatment used; T0: Without compost, TK1: 20 tons i ha-1 trichokomps, TK2: 30 tons i ha-1 trichocompos, BK1: 20 tons i ha-1 biodecompost, and i BK2: 30 tons i ha-1 biodecompost with observed variables, plant i height i, leaf width, number of branche and age of flower. The results i showed i that i on the observation of plant height, leaf width and i number i of branches in the administration of dose treatment TK1, TK2, BK1 and BK2 significantly different from the control treatment (T0. While the observation of flowering age showed that flowering age by giving TK1 treatment was significantly different from the control treatment (T0) but not significantly different from other treatments, namely TK2, BK1 and BK2. Giving doses of trichocompost and biodecompost as much as 20 tons ha-1 and 30 tons ha-1 did not give a different influence on the vegetative growth of Hiyung chili plants. This means that both the use of trichocompost and biodecompost can be applied to chili plants with only a dose of 20 tons ha-1.